WHOLE EXOME SEQUENCING OF A PATIENT WITH MORBID OBESITY: TRIO ANALYSIS, PRELIMINARY RESULTS - Sikhayeva , N.; Nakysh, A.; Utupov, T.; Zholdybayeva, E. (Eurasian Journal of Applied Biotechnology, 2023)
Morbid obesity is a severe form of obesity that leads to numerous cardiovascular, metabolic diseases and cancers, as well as increased mortality. Whole-exome sequencing is the effective tool for studying more extreme forms of disease, such as morbid obesity. The aim of the study is to identify candidate genes involved in the development of morbid obesity using whole exome sequencing. Here in this study, a family from Kazakh cohort having two siblings, one unaffected and one affected with morbid obesity was enrolled. Whole Exome Sequencing (WES) of trio with one affected and unaffected parents was done. The trio analysis revealed a number of potential candidate genes predisposing to morbid obesity. Three genetic models were used: recessive, de novo and compound heterozygote models. In the recessive model, one variant (rs116253946) in the KIAA1671 was identified as a candidate. In the de novo model, 15 polymorphisms located in 10 different genes were identified. In the compound heterozygote model, 6 polymorphisms, located in FRG1 and MST1L genes, were identified. This work presents the preliminary results of the study. Twelve genes identified by WES may be involved in the development of morbid obesity, and are grouped into three main pathophysiological pathways (immune response: MST1L, HLA-DRB5, PRRC2A, KIR2DS4; cell division and structure: CEP170, TEKT4; neuronal response: OR2T34, ANKMY2) or their function remains unknown to date (KIAA1671, TMEM191C, PPP6R2, FRG1).